A productions and operations management study on Ecolab Philippines, Inc. - Abad, George R. II (College of Engineering, 1999)
Ecolab Philippines Inc. is the leading global developer of premium cleaning, sanitizing and maintenance products and services for hospitals, and for institutional and industrial markets. Long before it has its first and only production plant in the Philippines, Ecolab has already provided customers with premium detergents, cleaners, sanitizers and conveyor lubricants to ensure clean and safe production by importing products from its different production facilities all over the world. Since the production plant was established at the Laguna Technopark Inc. in Sta. Rosa, Laguna last July of 1998, its products were already produced locally except for the electronic controls and dispensing equipment that enhance product usage. This study, with the aim to understand the production system of Ecolab Philippines, Inc. identifies, analyzes, and evaluates possible areas of intervention. This also provides a most effective opportunity for improving plant operations management. Plant visits were conducted and personnel involved in production were interviewed. Observation and documentation of the plant operation was done in the course of the study. Problems in forecasting method, plant layout, and space utilization were identified and their possible causes and effects were evaluated. It was found out that the forecasting done at the grass roots level is inaccurate and it was recommended that the Exponential Smoothing Method with smoothing constant equal to 0.6 be used to forecast demand. Large volume of finished goods inventory were also observed as an effect of inaccurate forecasts. As a result, half of the entire plant space is allocated to its storage. With the new forecasting method, monthly space requirement was determined and a new storage area layout was recommended. Plant layout was also evaluated and a new layout was proposed to improve material flow.